The Influence of Technopreneurial Learning on Technopreneurship Intention Students - Nurhayati, Dwi; Machmud, Amir (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Purpose: This study aims to determine and analyze the influence of technopreneurial learning for students technopreneurship intention. Methodology: The research method is used in an explanatory survey with hypothesis testing with data collection technique employed through questionnaires. The study population chosen were 344 students and the sample based on the formula Riduwan and Kuncoro was obtained as many as 185 students. The collected data were then analyzed using multiple regression techniques. Results: The results showed that the overall technopreneurial learning of students were categorized as effective and technopreneurship intention of students were categorized as high. It is known that technopreneurial learning variable have influence on the students technopreneurship intention with a coefficient of 0.455. Applications/Originality/Value: This finding implies that to improve student technopreneurship intentions, it is necessary to increase students technopreneurial learning with aspects contextual learning, personal and social training, and negotiated enterprise.